2017
DOI: 10.1021/acs.molpharmaceut.7b00321
|View full text |Cite
|
Sign up to set email alerts
|

RGD-Modified Albumin Nanoconjugates for Targeted Delivery of a Porphyrin Photosensitizer

Abstract: Advances in photodynamic therapy of cancer have been restrained by lack of cancer specificity and side effects to normal tissues. Molecularly targeted photodynamic therapy can achieve higher cancer specificity by combination of active cancer targeting and localized laser activation. We aimed to use albumin as a carrier to prepare targeted nanoconjugates that are selective to cancer cells and smaller than conventional nanoparticles for superior tumor penetration. IRDye® 700DX (IR700), a porphyrin photosensitize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 72 publications
2
33
0
Order By: Relevance
“…Li et al described, on the other hand, a covalent hybrid of IR700DX, a commercially available Si(IV)Pc, and HSA bearing tumour targeting RGD peptides, connected through an oligoethylene glycol spacer. 125 Phototoxicity studies in ovarian cancer cells showed that cellular delivery with this conjugate occurred via an endocytosis process. Moreover, this multivalent biohybrid resulted in being highly specific towards carcinogenic cells, while cells that did not express a v b 3 integrin were not affected.…”
Section: Hybrids With Serum Proteinsmentioning
confidence: 99%
“…Li et al described, on the other hand, a covalent hybrid of IR700DX, a commercially available Si(IV)Pc, and HSA bearing tumour targeting RGD peptides, connected through an oligoethylene glycol spacer. 125 Phototoxicity studies in ovarian cancer cells showed that cellular delivery with this conjugate occurred via an endocytosis process. Moreover, this multivalent biohybrid resulted in being highly specific towards carcinogenic cells, while cells that did not express a v b 3 integrin were not affected.…”
Section: Hybrids With Serum Proteinsmentioning
confidence: 99%
“…[30,31] In other way, a commercially Si(IV)Pc (IR7000DX) has been linked to HSA and RGD peptides, and the production of 1 O 2 was measured in ovarian cancer cells. [32] These bioconjugates demonstrated to be non-toxic to normal cells, and showed good results in cellular penetration and phototoxicity.…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…After that, AMD-PEG-BSA was synthesized based on the reaction mechanism that the amino group on BSA surface reacts with the NHS ester of AMD-PEG-NHS could form amide bond when stirring at room temperature, according to procedures reported previously with some modifications. 22 In brief, AMD-PEG-NHS was reacted with BSA at a molar ratio of amino group on BSA and NHS on AMD-PEG-NHS at 1:1.5, the pH of BSA solution was adjusted by NaHCO 3 to around 7.4, followed by adding AMD-PEG-NHS to react for the whole night at room temperature. The obtained product was purified using ultracentrifugal filter tube (MWCO: 5KDa), and the filtrate was lyophilized to calculate the yield.…”
Section: Synthesis and Characterization Of Amd-peg-bsamentioning
confidence: 99%